2018
DOI: 10.4081/jlimnol.2018.1699
|View full text |Cite
|
Sign up to set email alerts
|

Ecological drivers of testate amoeba diversity in tropical water bodies of central Mexico

Abstract: Testate amoebae are unicellular organisms characterized by a shell-like test. Due to their potential use as bioindicators (and paleoindicators), these organisms have been increasingly studied in the last decade, particularly in temperate latitudes. This study's objective was two-fold: to identify the testate amoeba communities sampled from 29 water bodies in Mexico and to determine if their presence and distribution also made them suitable bioindicators for tropical latitudes. A total of 40 taxa were recorded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
2
7
1
Order By: Relevance
“…3). Both testate amoebae are typical opportunistic species, recorded in hostile conditions in tropical, subtropical and temperate environments with very low pH and high salinity, and even in badly polluted waters (Dalby et al, 2000;Patterson and Kumar, 2000;Escobar et al, 2005;Sigala et al, 2018). Our results confirm this interpretation, as these two taxa were found in sites with low dissolved oxygen concentrations (Fig.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…3). Both testate amoebae are typical opportunistic species, recorded in hostile conditions in tropical, subtropical and temperate environments with very low pH and high salinity, and even in badly polluted waters (Dalby et al, 2000;Patterson and Kumar, 2000;Escobar et al, 2005;Sigala et al, 2018). Our results confirm this interpretation, as these two taxa were found in sites with low dissolved oxygen concentrations (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…A few studies in the Neotropics identified the effect of dissolved oxygen on the structure of testate amoebae communities (Dalby et al, 2000;Roe et al, 2010;Sigala et al, 2018). Our goal was to evaluate the role of dissolved oxygen concentration in determining the structure and diversity of testate amoebae communities in lakes of the Lacandón Forest, Chiapas, México.…”
Section: Introductionmentioning
confidence: 99%
“…These global species richness patterns contrast with Latitudinal Diversity Gradient theory, that postulates increase of biodiversity from poles to the Ecuador (Mannion et al, 2014;Schumm et al, 2019). Interestingly, a similar pattern is observed in other aquatic microorganisms in the northern Neotropics, such as testate amoebae (Sigala et al, 2016;Sigala Regalado et al, 2018;Charqueño-Celis et al, 2019), chironomids (Hamerlík et al, 2018), andcladocerans (Vázquez-Molina et al, 2016;Wojewódka et al, 2016). The low species diversity per lake in the northern Neotropics may be related to local environmental and evolutionary processes that have taken place recently in the geological time, namely during the Pleistocene and Holocene.…”
Section: Geology As Determinant Of Biodiversity and Distribution In The Northern Neotropicsmentioning
confidence: 85%
“…However, this genus is ecologically versatile with some species also living on macrophytes (Scenario 1 and 2). Predominance of Goeldichironomus along with the presence of the testate amoeba Arcella discoides (Charqueño-Celis et al, 2020; Sigala Regalado et al, 2018) suggests hypoxic conditions, at least temporarily (Figure 2). Furthermore, high water levels with more diluted waters (low carbonate content) could have created unfavourable conditions for ostracod development.…”
Section: Discussionmentioning
confidence: 99%